Epidemiological and clinical patterns of presentation of surgical oncological emergencies of abdomen at a tertiary institution - Vijayakumar, Karikkili K.; Arun, Damodharan; Deshpande, Mayuresh M.; Moolchandani, Sandeep (International Surgery Journal, 2017)
Background: Oncological surgical emergencies of abdomen pose a typical problem for surgeons with respect to the choice of curative and palliative treatments and procedures in absence of opportunity for proper evaluation and support of multidisciplinary approach. For appropriate management, it is important to understand the epidemiological and clinical profile of this disease complex. Methods: A prospective analysis of abdominal emergencies encountered in emergency surgery department was done over a period of two years at a single institution and the malignancies were studied with respect to the pattern of clinical presentation and epidemiological characteristics. Results: At our centre, the incidence of intraabdominal oncological emergencies requiring surgery was found to be 6.56% of total emergent presentations excluding abdominal trauma cases. The overall mortality for study duration was 29% and the perioperative mortality within 30 days was 24%. Colonic malignancies (62%) and gastric malignancies (28%) were the most common to present as emergency. It was noted that small bowel (5%) and ovarian malignancy (5%) were not common. Perforation peritonitis was the only presentation as acute emergency in carcinoma stomach. In colonic malignancies, obstruction was the most common emergency presentation (92.5%) and perforation was an uncommon mode of presentation (7.5%). Conclusions: Surgical intervention appears to be unavoidable in the situation of a malignancy presenting as an emergency case, despite the awareness that most of these patients are going to have a limited life expectancy. A high rate of perioperative mortality is observed in emergent presentations of oncological abdominal emergencies.